2002
DOI: 10.1093/glycob/12.5.345
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chemically modified heparin on Chlamydia trachomatis serovar L2 infection of eukaryotic cells in culture

Abstract: The mechanism and inhibitors of Chlamydia trachomatis serovar L2 infection of eukaryotic host cells were studied using a tissue culture model infection system. Potent inhibition of infectivity was observed when elementary bodies (EBs) were exposed to heparin or when HeLa 229 cells were treated with heparinase. No significant inhibition was seen the other way around. The same potent inhibition was observed when EBs were exposed to chemically 2-O-desulfated heparin (2-ODS heparin), which is composed of repeating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…With deference to some previous interpretations (20,21,23,24), minor reductions in chlamydial attachment or infectivity for CHO-677, CHO-745, or CHO-761 mutant cells are insufficient to warrant a conclusion that host cell heparan sulfate serves as a receptor for chlamydiae. These reproducible reductions in infectivity appear to be an epiphenomenon of chemical mutagenesis unrelated to the mutant cell's lack of glycosaminoglycan production.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…With deference to some previous interpretations (20,21,23,24), minor reductions in chlamydial attachment or infectivity for CHO-677, CHO-745, or CHO-761 mutant cells are insufficient to warrant a conclusion that host cell heparan sulfate serves as a receptor for chlamydiae. These reproducible reductions in infectivity appear to be an epiphenomenon of chemical mutagenesis unrelated to the mutant cell's lack of glycosaminoglycan production.…”
Section: Discussionmentioning
confidence: 78%
“…Comprehensive characterization of CHO-761 has shown that it is as deficient in heparan and chondroitin sulfate biosynthesis as is CHO-745 (1, 7). It has previously been shown that sulfated oligosaccharides are required for competitive inhibition of chlamydial infectivity (5); however, consistent with the lack of a functional role for host cell glycosaminoglycans, Yabushita et al (24) found no inhibition of chlamydial infectivity for a mutant cell line deficient in sulfated glycosaminoglycans.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, the high concentrations of chlorate required to block Chlamydia infection are toxic to the host cells. Furthermore, F-17 cells deficient in 2-O-sulfation of heparan sulfate show no significant reduction in C. trachomatis infectivity compared with WT cells (32). Attempts at knockdown of the PAPST1 gene have achieved no better than a 20% reduction in 35 SO 4 incorporation, even with a 60% reduction in mRNA levels (25).…”
Section: Discussionmentioning
confidence: 98%
“…Heparatinase treatment of host cells prevented L2 infection and the HS-synthesis deficient CHO [99] cell line was less sensitive to infection.…”
Section: Helamentioning
confidence: 99%